Changes and development in solo valley farming systems, Indonesia - Prabowo, Dibyo (Food and Agriculture Organization of the United Nations, 1993)
A study was made of the farming systems in Java, Indonesia, in 1988, and results were compared with those of a similar study conducted in 1974, to determine the changes that had occurred. A traverse was selected along a route across the Solo Valley to cover a fairly complete range of agro-ecological zones. Eight semi-detailed descriptions are given of 9 farming systems: (1) the low-altitude system with mainly rice and sugar; (2) rice, sugar and tobacco (below 200 m); (3) mainly rice (200-500 m); (4) dairy cattle and mixed crops (200-700 m); (5) rice, potato and cloves (500-700 m); (6) mixed crops and forest (700-1000 m); (7) mixed crops and cattle (700-1400 m); (8) vegetables and cattle (1400-1600 m); and (9) temperate-zone vegetables (1600-1700 m). Major improvements were observed in health, education, transport and the standard of living in general, despite a population growth of 15-25%. Increases were observed in farm incomes (by 30-50% in real terms), crop yields and prices, the importance of dairy and beef cattle, the area under clove, sugar cane and temperate-zone vegetables, industries and commerce, especially in the low-altitude villages. Annexes are included which deal with: the domestic garden crop mixture; livestock feeds; soil fertility maintenance; dairy activity economics; a farming system economic model; plant production economics; and labour use and demand (CAB)